The Coldwell Alkaline Complex, Ontario: Magmatic Affinity as Determined by an Isotopic and Geochemical Study - Bohay, Trevor (My University, 1997)
The Proterozoic' Coldwell Alkaline Complex is the southernmost intrusion of a number of N -S trending igneous bodies occurring in the Midcontinental Rift system exposed in the Lake Superior area. The Coldwell complex is host to several Ni-Cu-PGEbearing intrusions two of which; the Two-Duck Lake intrusion (Marathon deposit) and the Geordie Lake gabbro (MacRae occurrence) have been investigated in some detail with respect to PGE mineralisation. Both of these have been suggested to have experienced crustal contamination in conjunction with mineralisation. As a test of this possibility, a detailed Sm-Nd, oxygen isotope, and whole-rock geochemical study of these mineralised occurrences as well as of the Dunlop occurrence and the Middleton occurrence, together with unmineralised rocks of the complex was undertaken. The primary objectives are to determine whether crustal contamination is indicated in mineralised rocks and to try and ascertain the nature of the magma which formed the complex.
The Coldwell complex is thought to have been formed by emplacement of magma at three intrusive centres. Sm-Nd data for rocks from these three centres reveal similar isotopic values, with slight variations; samples taken from the western gabbros exhibit eNd values averaging -0.9 ranging from -2.9 to 0.9, whereas rocks from the eastern margin and centre of the complex have eNd values of about an average of 0.5 ranging from -0.5 to 1.2 suggesting that the magma that formed these rocks has undergone a lesser degree of crustal contamination. This data, supported by oxygen isotope and wholerock geochemical information indicates that crustal contamination seems to play a small, and varied role in the genesis of the Coldwell magmas. The Nd isotope data all clusters at values for CHUR, which indicates that it has been enriched relative to the depleted mantle. It has been postulated that an enriched mantle plume resided under the rift and promoted rift-related magmatism. The data from this study would seem to support this supposition.
Geochemical parameters utilised to define fields to geochemically delineate possible end member contributors to this primarily plume-derived magma indicate, that in addition to small, variable amounts of assimilation of upper and lower crust, the plume magmas also interacted with the lithospheric upper mantle to a small degree.
Keywords: Magmatic Affinity; Isotopic; Geochemical; magma